MORFIN (MODIFIED ULTRAFILTRATION MACHINE) APLIKASI POLYSULPHONE MEMBRANE PADA SARI BELIMBING UKM MULYASARI - Mahartika, Aginta Friska; Pradnya Dewi, Desak Putu Ariska; Sulthon, Adimas; Susanto, Agus (Program Kreativitas Mahasiswa - Teknologi, 2014)
UKM Mulyasari is one of the starfruit juice producers in Agrosuko, Poncokusumo Malang. This UKM has beed produce since 2011 that have 4 employes with 50 carton/week and omzet Rp. 1000.000/week. UKM Mulyasari stillused conventional filtration filter system which causesseveral problemssuch as the formation of deposits, murky juiced produced, and short-shelf life of the starfruit juice. Therefore, we used ultrafiltration machine with polysulphone membrane and mesh as the filter medium to overcome these problem. Apllication of machine ultrafilration as well known MORFIN (Modified Ultrafiltration Machine) able to produce star fruit which reduce the bacterial ultrafiltration up to 85,5%, reduce pectin up to 53,33% and reduce the number of total dissolved solids up to 46,36%. Futhermore, a shellf life of fruit juice also increase from 10 days to 2 week, increasing of production from 50 cartons to 100 cartons eveery week, increasing of effectiveness workwhichrequires onlyone-timefiltrationfor 25minutes and development and diversification product in UKM Mulyasari.Keywords: Star fruit Juice, Murky, Filtration, Polyulphone, MORFIN